Real-world regorafenib use among patients with advanced gastrointestinal stromal tumor in the United States - Ryan A. Denu; Sreevalsa Appukkuttan; Brian Hocum; Nick Liao; Arvind Katta; Jihaeng Heo; Bridgette Schroader; Risho Singh; Svetlana Babajanyan; Neeta Somaiah (PLoS ONE, 2026)
Background Gastrointestinal stromal tumors (GIST) are the most common gastrointestinal soft tissue sarcoma. Tyrosine kinase inhibitors are guideline-recommended therapy; however, resistance often occurs, requiring subsequent therapy. Regorafenib is a multikinase inhibitor approved for third-line therapy. Real-world data surrounding regorafenib’s use and place in therapy are limited. Objective To understand real-world regorafenib utilization and patient characteristics among US patients with advanced GIST. Methods This retrospective cohort claims analysis used data from Merative™ MarketScan ® research databases and included patients with ≥1 pharmacy claim for regorafenib during the identification period (10/2015–5/2023) and ≥1 GIST diagnoses any time prior to/on index date (first regorafenib prescription claim). Primary outcomes included duration of therapy (DOT) and time to next therapy (TTNT). Outcomes were stratified based on prior GIST treatment during the baseline period (BL) and initial regorafenib dose (i.e., low dose [LD] or regorafenib standard dose [RSD]) as of the index date. Results Nearly half (45.2%) of patients received imatinib and sunitinib prior to regorafenib initiation, and 73.5% received RSD. Patients who received prior imatinib or sunitinib alone before regorafenib had a numerically longer median DOT with regorafenib than those who received both in the BL before regorafenib (142.5 days [IQR: 87–257.5] vs 95 days [IQR: 53–192]). Patients receiving LD and RSD demonstrated similar median DOT (103.0 days [IQR: 41.5, 210.5] vs 94.5 days [IQR: (35.0, 171.0]) and TTNT (143 days [IQR: 70–293] vs 141 days [IQR: 77–191]). Conclusions Patients on LD and RSD had similar DOT and TTNT. Acknowledging the limitations from this real-world data, patients with prior imatinib or sunitinib alone appeared to have longer DOT on regorafenib than those who received both. Further research is warranted to explore the clinical benefits of these differences.